Design status of the ESS cryogenic moderator system. Issue 1 (March 2020) - Tatsumoto, H; Lyngh, D; Beßler, Y; Klaus, M; Hanusch, F; Arnold, P; Quack, H
Abstract: The Cryogenic Moderator System (CMS) has been designed to cool high-energy neutrons down to cold neutrons in two cryogenic hydrogen moderators (four ones in the future) by forced flow of subcooled liquid hydrogen at 17 K and 1.0 MPa. At 5 MW proton beam power, an estimated nuclear heating of 6.7 kW (17.3 kW in the future) is generated in the moderators. The subcooled liquid hydrogen is circulated by two pumps arranged in series with a mass flow rate of 1 kg/s to maintain the average temperature rise over each moderator below 3 K and is cooled through a plate fin heat exchanger by a helium refrigerator with a cooling capacity of 30.3 kW at 15 K. The ESS moderator vessels are optimized for maximum cold neutron brightness and pure para-hydrogen, requiring a para concentration of > 99.5 %. An ortho-para-hydrogen convertor is integrated into the loop along with an online para-hydrogen measurement system. The pressure fluctuation caused by unpredictable abrupt changes of nuclear heating will be mitigated using a pressure control buffer with a volume of 65 1.